Comfort in an instant : 75 comfort food recipes for your pressure cooker, multicooker + Instant pot - Clark, Melissa (Clarkson Potter/Publishers, 2018)
With 75 all-new recipes--50 of which can be made in under an hour start to finish--Melissa Clark brings her easy sophistication to comfort food classics for any electric pressure cooker, multicooker, or Instant Pot. The electric pressure cooker makes getting meals on the table fast, convenient, and utterly delicious--and with less mess and stress than any other kitchen appliance. In Comfort in An Instant, Melissa Clark elevates the classics with her trademark deep flavors and special spins--without ever sacrificing ease: * Sriracha Turkey Meatloaf * Pesto Risotto with Cherry Tomatoes * Classic Matzo Ball Soup * Easy Weeknight Chili * Lemon Chicken With Garlic + Olives * Pimento Mac + Cheese * Chipotle Pork Tacos * Flourless Chocolate Truffle Cake Innovative and practical, Comfort in an Instant sets the gold standard for flavor, quality, and convenience.